Assessing nitrogen flow and nitrogen footprint in the food system of a subtropical island with a scenario to mitigate nitrogen load impacted by trade-dependent agriculture - Kosuke Hamada; Sadao Eguchi; Nanae Hirano; Kei Asada; Naoko Oka (Environmental Research Letters, 2023)
Recent hikes in fertilizer, feed, and food prices threaten the food security of island-dwelling people who rely heavily on imports to sustain food supply and production. The influx of reactive nitrogen (Nr) through imports increases nitrogen load and degrades the environment. To overcome these problems, a robust and sustainable food system must be developed. In this study, we aimed to evaluate the present nitrogen flow in the food system of Ishigaki Island, located in the subtropical zone of Japan, and propose a measure to improve it based on the nitrogen footprint concept. Results showed that the major Nr-loss pathways for agricultural activity on the island were ‘crop-unused’ (37%) and ‘manure’ (43%). In food production, most of the Nr loss to the environment was related to export products, and less than 30% was related to island consumers. To meet the demand of food supply on the island, 5.1 times greater amount of food Nr than that of produced for island consumers was imported from overseas regions, placing the burden of Nr loss on such regions. We found that agricultural activities on the island mainly used chemical fertilizer; less than 13% of cattle manure was reused. To reduce the influx of Nr, we created a scenario in which 30% of chemical fertilizer was replaced by cattle manure. Results indicated 70% of the cattle manure produced on the island was necessary to achieve this scenario. This system could reduce Nr imports and Nr loss on the island by 16% and 17%, respectively. The proposed food system can be extended to other islands to overcome the recent price hikes and conserve the environment. This study is the first to present a detailed nitrogen flow in the food system of a tropical/subtropical island by using the nitrogen footprint concept.